2020
DOI: 10.14202/vetworld.2020.661-668
|View full text |Cite
|
Sign up to set email alerts
|

In vitro rumen biohydrogenation of unsaturated fatty acids in tropical grass-legume rations

Abstract: Aim: The aim of this study was to evaluate the effects of various combinations of tropical grass-legume species in rations on the biohydrogenation (BH) activity of unsaturated fatty acids (FAs), C18:0 composition, and fermentation profile in an in vitro rumen system. Materials and Methods: Samples of the following five fodder plants were used: One species of grass (Pennisetum purpureum) and four species of tree legumes (Leucaena leucocephala, Gliricidia sepium, Calliandra calothyrsus, and Indigofera z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
1
8
2
Order By: Relevance
“…Thus, it is likely that NH 3 production could support microbial protein synthesis, indicating that the inclusion of legumes (I. zollingeriana and Leucaena leucocephala) provides organic matter for rumen microbial protein synthesis. This is in agreement with the findings of a previous study [33] that inclusion of I. zollingeriana at a high proportion provided sufficient organic material for rumen microbes, increased the fermentability profile, and increased the rate of rumen microbial protein synthesis.…”
Section: Rumen Fermentation Characteristicsupporting
confidence: 93%
“…Thus, it is likely that NH 3 production could support microbial protein synthesis, indicating that the inclusion of legumes (I. zollingeriana and Leucaena leucocephala) provides organic matter for rumen microbial protein synthesis. This is in agreement with the findings of a previous study [33] that inclusion of I. zollingeriana at a high proportion provided sufficient organic material for rumen microbes, increased the fermentability profile, and increased the rate of rumen microbial protein synthesis.…”
Section: Rumen Fermentation Characteristicsupporting
confidence: 93%
“…Some reports have varying results, which may be due to different varieties, periods of sample collection, and soil types. In this study, L. leucocephala leaf contained 24.5% of CP, while the study by Makmur et al [22] reported that L. leucocephala contained 21%-25% of CP. This result is similar to this study.…”
Section: Discussioncontrasting
confidence: 49%
“…It may be because of the dietary substrate sampling Superscripts differences in the same column show significant differences among. p < 0.05 treatment method; the previous study by Makmur et al [22] collected all parts of plants, such as the leaves, flowers, and soft stems to investigate the chemical composition of each sample. However, this experiment used only the leaves of L. leucocephala.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result can be a consequence of the plant FA composition. Makmur et al (2019) analyzed the fatty acids of a tropical grass and different legumes and, although the concentration of the lipids in the pasture is relatively small, they found a greater amount of PUFA in tropical legumes. In the same way, different studies (Ponnampalam et al, 2017;Turner et al, 2014;Vasta et al, 2009;Lourenço et al, 2008) report the importance of the legume as a potential source to increase the unsaturated FA in the meat.…”
Section: Discussionmentioning
confidence: 99%